van't Hoff enthalpies without baselines. - John, D. M. (Cold Spring Harbor Laboratory Press, 2000)
Analysis of thermal melting curves represents one important approach for evaluating protein stability and the consequences of amino acid substitution on protein structure. By use of the van't Hoff relationship, the differential melting curve can be robustly fit to only three parameters, two of which are the underlying physical constants of melting temperature (Tm) and van't Hoff enthalpy (deltaHvH). Calculated Tm and deltaHvH values are insensitive to the choice of pre- and post-transition baselines. Consequently, the method accurately computes Tm and deltaHvH for extremely truncated data sets, in the complete absence of baseline information, and for proteins with low melting temperatures, where the traditional direct approach routinely fails. Moreover, agreement between deltaHvH values obtained using points derived from pre- vs. post-transition data provide an independent method for detecting some classes of non-two-state transitions. Finally, fitting of the differential denaturation curve should prove useful for analysis of abbreviated data sets obtained from high throughput array analysis of protein stability.